The shale oil revolution and the global oil supply curve. (4th December 2022) - Foroni, Claudia; Stracca, Livio
Summary: We focus on the implications of the shale oil boom for the global supply of oil. In order to derive testable implications, we introduce a simple stylized model with two producers, one facing low production costs and one higher production costs but potentially lower adjustment costs, competing à la Stackelberg . We find that the supply function is flatter for the high cost producer and that the supply function for shale oil producers becomes more responsive to demand shocks when adjustment costs decline. On the empirical side, we apply an instrumental variable approach using estimates of demand‐driven oil price changes derived from a standard structural VAR of the oil market. A main finding is that global oil supply is rather vertical, with a short‐term elasticity around 0.05. A rolling sample reveals that the shale oil boom does not appear to have fundamentally changed the contours of global oil production, but there is evidence for the oil supply curve to become more vertical in Saudi Arabia and more price responsive in the United States.